Implementasi Etika Bisnis dalam Menjalankan Bisnis pada UMKM Kerupuk Ibu Ramlah - Kartin Aprianti; Naurah Islami Pasha; Puput Jahsinia Putri (Jurnal Kabar Masyarakat, 2025)
The implementation of business ethics has become a crucial element in running a business, including at the scale of Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the application of business ethics in the operations of the Kerupuk Ibu Ramlah MSME. The study explores ethical business principles such as honesty, responsibility, transparency, and fairness, as applied in production, marketing, and relationships with consumers and business partners.The method offered to partners/MSMEs includes education/socialization through the use of leaflets, delivered door-to-door. The material provided in the leaflet covers the following topics: (1) The Role of Ethics in Business for MSME actors, (2) The Benefits of Ethics in Business for MSME actors, and (3) The Application of Ethical Principles in Business in financial, marketing, production, and human resource activities. However, challenges such as limited knowledge and resources affect the consistency of implementing business ethics. This study concludes that the implementation of business ethics contributes positively to the sustainability and reputation of MSMEs and recommends enhancing understanding and training in business ethics to strengthen business competitiveness.